2008
DOI: 10.1007/s10071-008-0174-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantity judgments of sequentially presented food items by capuchin monkeys (Cebus apella)

Abstract: Recent assessments have shown that capuchin monkeys, like chimpanzees and other Old World primate species, are sensitive to quantitative differences between sets of visible stimuli. In the present study, we examined capuchins' performance in a more sophisticated quantity judgment task that required the ability to form representations of food quantities while viewing the quantities only one piece at a time. In three experiments, we presented monkeys with the choice between two sets of discrete homogeneous food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
75
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 24 publications
6
75
0
Order By: Relevance
“…In this study, the crows needed more than twice the numerical distance to reach similar performance accuracy as monkeys and humans with similar dot displays [45,46,57,64,65]. This inferior discrimination performance may indicate more limited numerical capacities in crows, which was also indicated for other songbirds [66].…”
Section: (A) Analogue Number Representations In Crowsmentioning
confidence: 55%
“…In this study, the crows needed more than twice the numerical distance to reach similar performance accuracy as monkeys and humans with similar dot displays [45,46,57,64,65]. This inferior discrimination performance may indicate more limited numerical capacities in crows, which was also indicated for other songbirds [66].…”
Section: (A) Analogue Number Representations In Crowsmentioning
confidence: 55%
“…These relativenumerosity-discrimination experiments typically show that accuracy is a function of both the relative difference between the two numerosities and the magnitude of the numerosities, a property that obeys Weber's law of scalar variability. That is, both human and nonhuman subjects' accuracy at judging the difference between 5 and 10 items is similar to their accuracy at judging the difference between 20 and 40 items (Brannon, 2006;Evans, Beran, Harris, & Rice, 2009;Feigenson et al, 2004;Gallistel, 1989;Nieder, 2005;Whalen, Gallistel, n & Gelman, 1999). Although much research has been done with the simultaneous procedure, Rilling (1993) …”
Section: Relative Number Discriminationsmentioning
confidence: 99%
“…Across all set sizes, success was determined by the ratio between sets, not on the basis of the magnitude of the sets. Subsequent use of the one-by-one sequential presentation method with rhesus monkeys (Beran, 2007), capuchin monkeys (Beran et al, 2008;Evans et al, 2009), gorillas, bonobos, and orangutans (Hanus and Call, 2007), and even adult humans who were prevented from counting the arrays (Beran et al, 2006) indicated this same relation between performance and ratio between sets. This suggests that a similar mechanism may be operating across species to facilitate performance on this task.…”
mentioning
confidence: 99%